Condições periodontais e ocorrência de microrganismos periodontopatogênicos em pacientes com dependência química - Vieira, Ana Paula Miranda [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The drug addiction has acquired global dramatic aspects in terms of its dimensions and the effects it imposes on its users. These chemicals can reduce immune reactivity and tissue repair and enhance the microbial aggression, aggravating the destruction of periodontal tissues among other side effects. This study aimed to evaluate the presence of the major periodontal pathogens in the mouth of drug addict patients, comparing them to individuals who do not have this drug addiction, as well as assessing whether oral conditions affect the occurrence of these microorganisms. Therefore, we obtained data on systemic health, socioeconomic status, consumption of medicinal drugs, use of legal or illegal drugs on 200 patients with addiction kept in clinical detoxification, and an equal number of non-dependent patients, who constituted the control group. Clinical examinations were performed intra and extraoral and were collected samples of subgingival and supragingival biofilm, saliva and mucosa. The presence of Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis, Prevotella intermedia, P. loescheii, P. nigrescens, Tanerella forsythia and Treponema denticola was assessed by polymerase chain reaction (PCR). Possible associations between different infectious agents were evaluated using the Spearman correlation test, while the Chi-square test was used to determine correlations with clinical parameters. The results showed an increase in the frequency of the main oral anaerobes, particularly in supragingival plaque, although the presence of these microorganisms in other clinical specimens has also been observed. The oral colonization showed higher correlation with periodontal condition than any pattern of consumption of legal and/or illegal drugs

A dependência química adquiriu aspectos dramáticos globais em função de suas dimensões e dos efeitos que impõe aos atingidos. Esses agentes químicos são capazes de reduzir a reatividade imunológica e o reparo tecidual, além de potencializar a agressão microbiana, agravando a destruição do periodonto e outros efeitos colaterais. Esse estudo objetivou avaliar a presença dos principais patógenos periodontais na boca de pacientes dependentes, comparando-os com indivíduos que não apresentam essa dependência, bem como avaliar se as condições bucais afetam a ocorrência desses microrganismos. Para tanto, foram obtidos dados referentes às condições de saúde sistêmicas, socioeconômicas, consumo de medicamentos, uso de drogas lícitas ou ilícitas de 200 pacientes com dependência química mantidos em clínica de desintoxicação e igual número de pacientes não dependentes, que constituíram o grupo controle. Foram realizados exames clínicos intra e extrabucais e foram coletadas amostras de biofilme subgengival e supragengival, saliva e mucosas. A presença de Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis, Prevotella intermedia, P. loescheii, P. nigrescens, Tannerella forsythia e Treponema denticola foi avaliada por meio da reação em cadeia da polimerase (PCR). As possíveis associações entre os diferentes agentes infecciosos foram avaliadas por meio do teste de correlações de Spearman, enquanto o teste de Qui-quadrado foi empregado para determinar as correlações com os parâmetros clínicos. Os resultados mostraram um aumento na frequência dos principais anaeróbios bucais, em particular no biofilme supragengival, embora a presença desses microrganismos nos demais espécimes clínicos também tenha sido observada. A colonização bucal mostrou maior relação com a condição periodontal do que com qualquer padrão de consumo de drogas lícitas e/ou ilíitas
Keywords: Drogas; Vício em drogas; Periodontite; Drugs